Shining a light on organisational risk. Issue 10 (October 2021) - Hodler, Amy
Abstract : When we consider how to rein in and limit nefarious activity on organisational networks, it helps to think like the individuals behind the attacks. In short, it pays to 'think like a criminal' to respond better to any attack.